The Effectiveness of Self-Directed Learning on The Professional Development of Pre-Registration Nursing Students: - Yusra Al-Nasseri (Kufa Journal for Nursing Sciences)
Background: The nature of the nursing profession requires professionals who are confident, responsible, motivated and able to work and respond independently in a changing health care environment (Garrison 1992). Hence, the trend in nursing education has moved towards an adult approach to teaching in which students must be self-directed to be able to meet the new challenges. Self directed learning (SDL) approach is one of the programmers which has been established based on adult teaching approach. SDL does not only provide a means for effective learning of knowledge and skills but also serves as a vehicle for enabling nursing students to acquire and develop independent learning skills; as well as develop a sense of accountability and responsibility that equips them with the essential attributes they require for their future nursing career.